2010
DOI: 10.1038/jcbfm.2010.87
|View full text |Cite
|
Sign up to set email alerts
|

PET Scan Perfusion Imaging in the Prader–Willi Syndrome: New Insights into the Psychiatric and Social Disturbances

Abstract: The Prader-Willi syndrome (PWS), a rare multisystem genetic disease, leads to severe disabilities, such as morbid obesity, endocrine dysfunctions, psychiatric disorders, and social disturbances. We explored the whole brain of patients with PWS to detect abnormalities that might explain the behavioral and social disturbances, as well as the psychiatric disorders of these patients. Nine patients with PWS (six males, three females; mean age 16.4 years) underwent a positron emission tomography (PET) scan with H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 32 publications
2
27
1
1
Order By: Relevance
“…In contrast, in the temporal lobe, there are centers responsible for processing auditory information and understanding of spoken language, the failure of which may result in problems with communication. Interestingly, similar changes in brain neuroimaging are observed in patients with autism [56]. This study is consistent with the ones described previously.…”
Section: Neuroimaging Studies Of the Brain In Pws And Schizophreniasupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, in the temporal lobe, there are centers responsible for processing auditory information and understanding of spoken language, the failure of which may result in problems with communication. Interestingly, similar changes in brain neuroimaging are observed in patients with autism [56]. This study is consistent with the ones described previously.…”
Section: Neuroimaging Studies Of the Brain In Pws And Schizophreniasupporting
confidence: 93%
“…Reduced volume of grey matter was more extensive in PWS patients with deletion and male gender in schizophrenia [53,54]. Studies on regional cerebral flow (rCBF) in positron emission tomography (PET) revealed areas of hypoperfusion in the anterior cingulate and the upper part of the temporal lobe in PWS patients [56]. Changes observed in the functional neuroimaging refer to the structures responsible for regulation between cognitive and emotional processes, pain perception, empathy and motivation.…”
Section: Neuroimaging Studies Of the Brain In Pws And Schizophreniamentioning
confidence: 99%
“…Moreover, emerging functional neuroimaging evidence indicates the presence of hyper‐responsive neural networks that involve brain regions, such as the hypothalamus, ventromedial prefrontal cortex, and insula, as well as heightened reward circuitry activation in PWS in response to food stimulation [Dimitropoulos et al, ; Holsen et al, ; Mantoulan et al, ; Miller et al, ; Moran and Westerterp‐Plantenga, ; Ogura et al, ; Shapira et al, ]. Compared with body mass index (BMI)‐matched non‐PWS obese subjects, PWS subjects exhibited hyper‐activations in the subcortical reward circuitry and hypo‐activation in cortical inhibitory regions [Holsen et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…De plus, les études d'imagerie fonctionnelle cérébrale montrent qu'il existe des anomalies très variées de perfusion et de métabolisme qui ne touchent pas seulement l'hypothalamus. Il existe en effet de nombreuses altérations dans le réseau neuronal régulant l'appétit, qui implique en particulier l'hypothalamus, le cingulum antérieur, le cervelet, le cortex préfrontal et l'insula [9][10][11]. Il semblerait que ce soit surtout un défaut de contrôle de la prise alimentaire qui sous-tende le comportement alimentaire.…”
Section: Diagnosticunclassified